CONFLICT MEDIATION IN DIVORCE CASES WITH CHILDREN: CONTRIBUTIONS OF PSYCHOLOGY - Alves, Vinicius Guimarães; de Brito, Lara dos Santos; Feijó, Marianne Ramos; Junior, Edward Goulart; Valerio, Nelson Iguimar (Seven Editora, 2024)
The article aims to discuss the contributions of Psychology in the Brazilian judicial system in cases of divorce with children aged up to 18 years. For the preparation of the theoretical essay, the techniques used and the challenges encountered by professionals working with mediation practices in the judicial system were investigated, through a bibliographic review in the CAPES, Scielo and Google Scholar databases, with priority for works published between the years 2019 and 2023. The works, selected in accordance with the specificity of the study, provided relevant information about the reality of the psychologist who works as a mediator in Brazil. The results highlight the interdisciplinary nature of their work, the scarcity of longitudinal research with a robust theoretical basis for action, challenges to demarcate the limits, as well as evidenced the precarious working conditions to which mediators, mostly women, are subjected, influencing the scenario and the need for future research. DOI: https://doi.org/10.56238/sevened2024.037-067